MSP 13 PRODUCTIVITY USING RICE TRANSPLANTER - Harini, Nyang Vania ayuningtyas; Ilmiasari, Yeyen; Ahmal, Vicko Javier (Jurnal Agrotek Tropika, 2025)
Rice is food majority of Indonesia's population, Indonesia's rice production decreases every year. The decline in national rice production is caused including low rice productivity, land conversion and inappropriate cultivation techniques. Need made to increase productivity, in this research using quality seeds, namely MSP 13 and applying Rice Transplanter technology. Apart seeds, the process of cultivating rice from planting rice seeds in rice fields. Technology for planting rice seed using Rice Transplanter currently being developed in several regions. The experience this technology shows that planting time is more efficient. Quality of rice plants is better, especially the early vegetative fase. From several studies that the use of Rice Transplanters and superior seeds rice productivity up to 7%. This research aims determine the productivity of MSP 13 using Rice Transplanters carried out in Daya Asri, Tumijajar District, West Tulang Bawang Regency. The design used in this study was a non-factorial Completely Randomized Design (CRD), namely: P1 = Using a Rice Transplanter, P2 = Manual repeated 5 times, there 10 units and BNT testing. Tools and materials, Rice Transplanter, hand tractor, hoe, plot board, meter, and stationery, MSP 13 seeds, NPK, dolomite, insecticides. Harvest 105 days after sowing. The results study use Rice Transplanter on MSP 13 rice affect plant height with the best height of 80.33 cm, the number of tillers 21.6 tillers, number of panicles 16.8 panicles at 45 HST. At harvest weight of 42.1 gr / sample, and productivity of 8.25 tons ha-1 GKP or 0.825 kg ha-1 GKP.